Islamic Entrepreneurial Ecosystem: Model Integratif antara Etika Syariah, Kewirausahaan, dan Keberlanjutan Sosial - Peni Indrawati (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2025)
This study highlights the Islamic Entrepreneurial Ecosystem (IEE) as a new paradigm in Islamic entrepreneurship development that integrates spiritual values, economic innovation, and social responsibility within a systemic framework. Through a conceptual approach, the research proposes an integrative model grounded in sharia ethics as the moral foundation, innovative entrepreneurship as the driving mechanism, and social sustainability as the ultimate orientation. The IEE model emphasizes that Islamic economics goes beyond growth and efficiency, aiming instead at falah—a holistic well-being encompassing both material and spiritual dimensions. Core ethical principles such as honesty (sidq), justice (‘adl), trustworthiness (amanah), and social benefit (maslahah) guide economic activities in alignment with the objectives of maqashid al-shariah. Furthermore, the entrepreneurial dimension promotes value-driven innovation, positioning Muslim entrepreneurs as agents of social transformation who contribute to sustainable development. The model also underlines the collaborative role of ecosystem actors—government, Islamic financial institutions, academia, entrepreneurs, and society—in building an inclusive, just, and resilient economic system. Theoretically, IEE expands conventional entrepreneurial ecosystem frameworks by embedding moral and spiritual dimensions; practically, it serves as a guideline for public policy formulation and sharia-compliant business strategies that are both equitable and sustainable. Therefore, IEE offers a blueprint for modern Islamic economic development that is rooted in spiritual values, adaptive to innovation, and oriented toward the collective welfare (maslahah) of humankind